17. Pain modulation in patients with Multiple Sclerosis, pain and spasticity after oromucosal cannabinoid spray (THC/CBD): A study with quantitative sensory testing and laser evoked potentials. Issue 4 (April 2016) - Turri, M.; Donato, F.; Teatini, F.; Zanette, G.; Tugnoli, V.; Deotto, L.; Moretto, G.; Squintani, G.
Abstract : Oromucosal cannabinoid (THC/CBD) spray administration for the treatment of pain in patients affected by Multiple Sclerosis (MS) has been well documented and MS patients generally complain of different kind of pain, including spasticity-related and neuropathic pain. Our purpose was to examine pain modulation and thermal/pain threshold of MS patients before and after THC/CBD. 16 MS patients underwent clinical examination (including NRS scale), Quantitative Sensory Testing (QST) and Laser Evoked Potentials (LEPs) before and after one month of oromucosal spray. Psychophysiological and neurophysiological testing were compared to sex- and age-matched controls. Patients reported a significant reduction in pain (NRS 7, 2 /4, 7 before/after THC/CBD); QST thresholds were altered in patients and did not change after THC/CBD; there was a significant reduction of LEPs amplitude and increase of LEPs latency in MS patients compared to controls and no significant threshold or LEPs parameters change was noted after drug administration. Our results suggest that THC/CBD is effective on pain but LEPs and QST are not sensitive enough to detect pain modulation; the fact may be dependent on different factors, including the high disease burden as well as different kind of pains (nociceptive and neuropathic) affecting MS patients.